2017
DOI: 10.1016/j.bmc.2017.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Simplifying nature: Towards the design of broad spectrum kinetoplastid inhibitors, inspired by acetogenins

Abstract: The need for new treatments for the neglected tropical diseases African sleeping sickness, Chagas disease and Leishmaniasis remains urgent with the diseases widespread in tropical regions, affecting the world's very poorest. We have previously reported bis-tetrahydropyran 1,4-triazole analogues designed as mimics of the annonaceous acetogenin natural product chamuvarinin, which maintained trypanocidal activity. Building upon these studies, we here report related triazole compounds with pendant heterocycles, mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…The same work of Gould et al (2017) [77], evaluated anti-Trypanosoma brucei activity of the chamuvarinin (Figure 12) analogs, where, of the whole series of triazole compounds obtained, only compound 31 (Figure 12) demonstrated an increase in the anti-T. brucei activity, when compared to chamuvirinin, with IC50 of 0.037±0.003 µM, not being cytotoxic in HeLa cells, but with an EC50 value of [80] reported the azole action as a binder to DNA minor grooves, which inhibits the protein-DNA interaction, being of useful application in parasite infections treatment, among others diseases [81], by inducing apoptosis of invasive cells. Distamycin, a polyamide natural product which act as binder to DNA minor groves, was used as base for prepare a series of analogs, where five derivatives (Figure 14) demonstrated anti-Trypanosoma brucei activity in the nanomolar range (IC50 > 40 nM).…”
Section: Antitrypanosomal Activity: Trypanosoma Bruceimentioning
confidence: 79%
See 1 more Smart Citation
“…The same work of Gould et al (2017) [77], evaluated anti-Trypanosoma brucei activity of the chamuvarinin (Figure 12) analogs, where, of the whole series of triazole compounds obtained, only compound 31 (Figure 12) demonstrated an increase in the anti-T. brucei activity, when compared to chamuvirinin, with IC50 of 0.037±0.003 µM, not being cytotoxic in HeLa cells, but with an EC50 value of [80] reported the azole action as a binder to DNA minor grooves, which inhibits the protein-DNA interaction, being of useful application in parasite infections treatment, among others diseases [81], by inducing apoptosis of invasive cells. Distamycin, a polyamide natural product which act as binder to DNA minor groves, was used as base for prepare a series of analogs, where five derivatives (Figure 14) demonstrated anti-Trypanosoma brucei activity in the nanomolar range (IC50 > 40 nM).…”
Section: Antitrypanosomal Activity: Trypanosoma Bruceimentioning
confidence: 79%
“…INSERT FIGURE 11 HERE Gould et al (2017) [77] have reported bis-tetrahydropyran 1,4-triazole analogs drawn as mimics of the annonaceous acetogenin natural product chamuvarinin (Figure 12), which maintained trypanocidal activity. This acetogenin compounds are polyketides found in Annonaceae spp [78].…”
Section: Antitrypanosomal Activity: Trypanosoma Cruzimentioning
confidence: 99%
“…However, the original squamocin molecule was drastically denatured, since it had its characteristic γ-butyrolactone final ring and the ether groups removed. The most remarkable point in the mimic structure produced by Gould is the tetrahidropyrane core connected to the triazole ring, that replaces the bis-THF of squamocin [ 85 ]. Similar approaches were implemented by Ichimaru et al, where bullatacin mimics were synthesized employing piperazine core.…”
Section: Annona Cherimola Mill Acetogenin Derivativesmentioning
confidence: 99%
“…19 We also report extended phenotypic screening of the related kinetoplastids T. cruzi, L. major and L. donovani. 20 Furthermore, as part of efforts to identify the protein target and establish the mode of action, we have adapted our core inhibitor scaffold to incorporate both a photo-reactive diazirine unit and an orthogonal reporter alkyne tag to produce photo-affinity labelling inhibitors. 21 Direct incorporation of a small photo-affinity label was viewed as advantageous in terms of minimising disruption of ligand-protein binding interactions in vitro, and reducing non-specific labelling by retaining the structural features identified by phenotypic screening, thereby increasing the likelihood of successful target protein labelling.…”
Section: Introductionmentioning
confidence: 99%
“…maintained activity when compared to 27. Inhibition activity is only moderately reduced with a bulky n-octyl substituent(20). The potency in other parasitic cell lines (insect forms of T. brucei, T. cruzi and L. major) were more sensitive to alkyl ether chain length.…”
mentioning
confidence: 97%